Microphysical Properties of Tropical Tropopause Layer Cirrus. Issue 11 (4th June 2018) - Woods, Sarah; Lawson, R. Paul; Jensen, Eric; Bui, T. P.; Thornberry, Troy; Rollins, Andrew; Pfister, Leonhard; Avery, Melody
Abstract: Pervasive cirrus clouds in the tropical tropopause layer (TTL) play an important role in determining the composition of stratospheric air through dehydration of tropospheric air entering the stratosphere. This dehydration affects Earth's energy budget and climate, yet uncertainties remain regarding the microphysical processes that govern TTL cirrus. TTL cirrus were sampled with the NASA Global Hawk UAV for over 30 hr in the Western Pacific in 2014 during the Airborne Tropical TRopopause EXperiment. In situ measurements by a Fast Cloud Droplet Probe and Hawkeye probe (combination Fast Cloud Droplet Probe, Two‐Dimensional Stereo optical array probe, and Cloud Particle Imager) provided particle concentrations and sizing between 1‐ and 1, 280‐μm diameter and high resolution images for habit identification. We present the variability in ice concentrations, size distributions, and habits as functions of temperature, altitude, and time since convective influence. Observed ice particles were predominantly small and quasi‐spheroidal in shape, with the percentage of quasi‐spheroids increasing with decreasing temperature. In comparison to the large fraction of the population consisting of quasi‐spheroids, faceted habits (columns, plates, rosettes, and budding rosettes) constituted a smaller percentage of the overall population and exhibited the opposite correlation with temperature. The trend of higher percentages of faceted crystals occurring at warmer temperatures may be due to diffusional growth or aggregation as particles descend through cloud, and/or the more rapid diffusional growth rate at warmer temperatures. Sampling was typically well away from deep convection, however, and very few aggregates were observed, so the trend of higher percentages of faceted habits is likely attributable to diffusional growth. Key Points: Ice particles were predominantly quasi‐spheroidal, especially at coldest temperatures Growth‐sedimentation is dominant in determining TTL cirrus size distributions and habits Aggregation is negligible in TTL in situ cirrus